The subject of criminal trespass in forensic characteristics of obstructing the lawful activities of the Armed Forces of Ukraine and other military formations - Vashchenko, O.A. (Аналітично-порівняльне правознавство, 2024)
The article states that Russia's military aggression against our country created, among other things, the need to make changes to domestic legislation in order to criminalize certain activities of people. In particular, by supplementing the Criminal Code of Ukraine with Article 114-1 "Obstructing the lawful activities of the Armed Forces of Ukraine and other military formations.” And with the beginning of the full-scale invasion of the territory of Ukraine, unfortunately, the number of the specified criminal offenses only increased: 7 criminal offenses in 2021, 76 in 2022, 159 in 2023. It has been established that the subject of a criminal offense in the studied category of criminal offenses will be the lawful activities of the Armed Forces of Ukraine and other military formations in a special period. It has been investigated that the Armed Forces of Ukraine are a military formation that, according to the Constitution of Ukraine, is entrusted with the defense of Ukraine, the protection of its sovereignty, territorial integrity and inviolability. And other military formations include the State Border Service of Ukraine, the Security Service of Ukraine, the State Special Service of Transport, the State Service of Special Communications and Information Protection of Ukraine, as well as the Foreign Intelligence Service of Ukraine It was concluded that the subject of criminal trespass is a criminal offense provided for in Art. 114-1 of the Criminal Code of Ukraine is the legal activity of the Armed Forces of Ukraine, the State Border Guard Service of Ukraine, the Security Service of Ukraine, the State Special Transport Service, the State Service for Special Communication and Information Protection of Ukraine and the Foreign Intelligence Service of Ukraine. The obstruction itself may consist of a certain intervention aimed at complicating the successful performance of the tasks of the Armed Forces and other military formations within the framework of their legitimate activities. Such obstacles can arise both in the form of actions that pose a threat to society, and in the form of inaction. In the first case, obstruction can be manifested in active measures aimed at creating physical barriers (for example, damage to vehicles) and/ or informational barriers (for example, spreading disinformation). In the second case, it may arise due to non-fulfillment or improper fulfillment of legal obligations (for example, sabotage), which as a result leads to the corresponding obstruction.